EFFECT OF CALORIC VESTIBULAR STIMULATION ON MEMORY - ASWATHY GOPINATH; ARCHANA R; KUMAR SAI SAILESH; MUKKADAN J K (International Journal of Pharma and Bio Sciences, 2015)
This study was undertaken to provide an authoritative database for beneficial effects of vestibular stimulation and to suggest vestibular stimulation as a therapy for enhancement of cognition. Vestibular stimulation is performed by caloric vestibular stimulation. Scopolamine is used to induce partial amnesia. T-maze task is used to record acquisition and retention of the memory score before and after vestibular stimulation. Memory scores were significantly different between scopolamine induced amnesia control and hot water vestibular stimulation groups (p<0.05). Memory scores between scopolamine induced amnesia cold and hot vestibular stimulation groups were highly significant. (p value <0.05). This study categorically confirms that caloric vestibular stimulation with hot water enhances cognition. Hence this study certainly merits further studies with higher sample size to confirm whether caloric vestibular stimulation can be recommended for enhancement of cognition.